Involvement im Fernstudium: Methoden und Instrumente zur Verbesserung von Involvement als qualitätssteigernder Aspekt virtueller Tutorien - Kirsten Oleimeulen (IUBH Internationale Hochschule, 2020)
– Virtual tutorials are the only interface to classroom teaching in distance learning. They correspond to lectures, seminars and exercises in direct study. Their designated position is committed to quality in order to keep distance learning competitive on the long run. High dropout rates already indicate a lack of binding quality in distance learning. The approach of involvement, as a person- and tutorial-related variable, is a predisposed possibility to increase the quality of education and loyalty of distance learning with very little resource expenditure. According to the typology of virtual models by Mason (1998), the degree of involvement is decisive for the quality of the model. Due to the high demands of distance learning on the self-management ability of the students, a high level of personal loyalty is necessary in order to absorb the feeling of lonely and alone learning. This can be counteracted through the feeling of belonging to a group or group awareness. This feeling that most students experience in direct study on their own must be actively generated in distance learning due to the mediating medium. The tools required for this are available on all common learning platforms, but their importance is not recognized. Involvement can also be created through active participation opportunities for learners. This includes the possibility of active communication in virtual tutorials, which can be guided by the tutors through skillful rhetorical means, as well as the active participation via shared screen functions, which gives participants writing, drawing and arithmetic possibilities in the shared virtual space, as well as the immediate publication of cell phone photos and thus current documents about the simultaneous entry to the zoom meeting with the cell phone. The importance of the tutorials can be taken into account when creating the curriculum. With the implementation of research-related teaching as one of the central tasks of university political education, the virtual tutorial is the only place for classroom teaching in distance learning. (Wissenschaftsrat, 2016) With the help of the matrix for the classification of research-oriented teaching by Rueß, J./Gess, C./Deicke, W. (2016), all 12 levels of research-related teaching can be incorporated into the curriculum of distance learning courses in order to fulfill the central task of teaching of research competencies. This involves communicative requirements in the form of discussion and exchange, which can only be realized through the online-based tutorial. The virtual tutorial thus represents a crucial quality component in distance learning as an education and interpersonal attachment factor.
Keywords: I19; 650; virtuelle Tutorien; Group Awareness; Bildungsqualität; Bindungsqualität; Ressourcen; Matrix forschungsorientierter Lehre; Involvement in virtuellen Modellen; Selbststeuerung; involvementförderliche Fragetechniken